Fasting triglyceride concentrations are associated with markers of lipid metabolism and glucose homeostasis in healthy, non-obese dogs in lean and overweight condition - Gomez-Fernandez-Blanco, Carlos; Peeters, Dominique; Farnir, Frédéric; Höglund, Katja; Gouni, Vassiliki; Wiberg, Maria; Lundgren Willesen, Jakob; Hanås, Sofia; McEntee, Kathleen; Tiret, Laurent; Häggström, Jens; Lohi, Hannes; et al. (Frontiers in Veterinary Science, 2024)
Serum triglyceride concentrations increase in dogs with obesity, which is typically assessed by body condition score (BCS), however little is known about changes that take place in non-obese dogs in overweight condition. Further, the associations of triglyceride levels with other markers of energy homeostasis are poorly characterised in healthy animals. The present study aimed to evaluate associations between both BCS and triglyceride concentrations with other markers of lipid and glucose metabolism in healthy, non-obese dogs, as well as to assess whether these markers change significantly in non-obese dogs with overweight as compared to their lean counterparts. Serum concentrations of cholesterol, free fatty acids, triglycerides, insulin, glucose and fructosamine were measured in 532 healthy, client-owned dogs, assigned either to ‘lean’ (BCS: 3–5) or ‘overweight’ (BCS: 6–7) categories. Generalised linear mixed models were used to assess associations between BCS categories, triglyceride concentrations and other variables, correcting for the effect of breed. Compared with lean dogs, overweight dogs had a greater serum cholesterol concentration (95% CI, 5.3–6.2 mmol/L or 205–237 mg/dL versus 5.1–5.4 mmol/L or 198–210 mg/dL, p = 0.0032), insulin concentration (95% CI, 17.5–22.1 μU/ml versus 16.7–18.0 μU/ml, p = 0.0374) and were older (95% CI, 4.0–5.3 versus 3.4–3.7 years, p = 0.0005). Triglyceride concentrations were positively associated with fructosamine (r2 = 0.31, p = 0.0012), cholesterol (r2 = 0.25, p < 0.0001), insulin (r2 = 0.14, p = 0.0030) and glucose (r2 = 0.10, p = 0.0014) concentrations, and negatively associated with free fatty acid concentrations (r2 = 0.11, p < 0.0001). However, there was no association between triglyceride concentrations and age. In conclusion, both BCS and triglyceride concentrations were associated with other markers of glucose and lipid metabolism in non-obese healthy dogs, amongst which those with overweight showed metabolic changes as compared to their lean counterparts. Triglyceride concentrations were associated with an increase in insulin and fructosamine concentrations that might reflect an early-phase impairment in glucose tolerance which, surprisingly, was concurrent with lower basal free fatty acid concentrations.